Illustrations of universal progress: a series of discussions - Spencer, Herbert (D. Appleton and Co., 1864)
Progress : its law and cause -- Manners and fashion -- The genesis of science -- The physiology of laughter -- The origin and function of music -- The nebular hypothesis -- Brain on the emotions and the will -- Illogical geology -- The development hypothesis -- The social organism -- Use and beauty -- The sources of architectural types -- The use of anthropomorphism.